Effectiveness of a novel augmented reality cardiopulmonary resuscitation self-training environment for laypeople in China: a randomized controlled trial. Issue 1 (29th November 2022) - Hou, Luoya; Dong, Xu; Li, Ke; Yang, Congying; Yu, Yang; Jin, Xiaoyan; Shang, Shaomei
Abstract : Abstract: Objectives: The training rate of cardiopulmonary resuscitation (CPR) among the general population in China is relatively low. Augmented reality (AR) may be an effective method of CPR training, especially where in-person interactions may not be possible. The purpose of this study was to analyze the effectiveness of AR CPR self-training for people who are not professional health care workers. Methods: A 2-arm and prospective randomized controlled trial was conducted. Participants were recruited via advertisements from August to October 2021 in Beijing and were randomly assigned to either an AR self-training CPR group (n=82) or an instructor-led training group (n=81). Participants in the AR group spent 25 minutes in a simulated environment using HoloLens to engage them in immersive multisensory CPR self-training. Participants in the instructor-led group received 25 minutes of CPR instruction with the guidance of a certified instructor. The outcomes, including the mean chest compression depth (centimeter) and rate (/min), the proportion of correct positioning of hands, correct rescue breaths, compression accuracy, and the proportion of participants that adhered to the American Heart Association's CPR guidelines, were compared between the 2 groups. Results: The median age of the participants was 23 years old (interquartile range: 22–25) and the median weight was 55 kg (interquartile range: 51–63). The mean difference (95% CI) in the compression rate between the 2 groups [mean (SD): AR 109.03 (2.68)/min vs. instructor-led 110.88 (3.03)/min] was −1.85 (−2.74 to −0.96)/min. The mean difference (95% CI) in the depth of compressions between the groups [mean (SD): AR 5.59 (0.59) cm vs. instructor-led 5.55 (0.47) cm] was 0.04 (−0.13 to 0.20) cm. The AR self-training was noninferior to the instructor-led CPR training, as measured by the rate and depth of compressions ( P <0.001). The proportion of participants that adhered to the AHA guideline for compression depth (AR: 65.85% vs. instructor: 72.84%, χ 2 =0.935, P =0.334) was similar in the 2 groups. The proportion of correct rescue breaths [AR: 64 (78.05%) vs. instructor: 74 (91.36%), P <0.001] were significantly higher in the instructor-led group. Heterogeneity of the effect of AR self-training on the chest-compression rate were found in subgroups of sex ( P =0.03 for the interaction) and weight ( P =0.03 for the interaction). Discussion: The AR self-training and instructor-led training are comparable in terms of both groups' compression rate and depth. This study may have important implications to improve the CPR training rates in China.